Predicting compressive strength of cementstabilized earth blocks using machine learning models incorporating cement content, ultrasonic pulse velocity, and electrical resistivity - Sathiparan, N.; Pratheeba, J. (Taylor & Francis, 2023)
The quality monitoring technique for Cement stabilised earth blocks (CSEBs) is so challenging that it is often neglected. This study has investigated the possibility of using machine learning to predict the compressive strength of CSEBs based on cement con-tent, electrical resistivity and Ultrasonic pulse velocity (UPV) as a potential way to enhance quality control. The study considered three types of soil and different cement content in the preparation of CSEBs with 10 different cement-soil mixtures. Various machine learning models were proposed to predict the compressive strength of CSEBs. The models were evaluated using 180 experi-mental datasets, and the best model for predicting the compressive strength of CSEBs was selected. The ANN and BTR models per-formed better than the other machine learning models tested in this study for predicting the compressive strength of CSEBs. The results show that a combination of cement content, electrical resis-tivity and UPV can be used to assess the quality of CSEBs more accurately, which can contribute to the knowledge base and be applied in the real world. Materials scientists and engineers can use reliable predictive models to assess the strength properties of both new and old brick structures without damage or loss of use
Keywords: CSEB; Compressive strength; UPV; Electrical resistivity; Machine learning